Oxysterol mixture and, in particular, 27‐hydroxycholesterol drive M2 polarization of human macrophages. (16th December 2015) - Marengo, Barbara; Bellora, Francesca; Ricciarelli, Roberta; De Ciucis, Chiara; Furfaro, AnnaLisa; Leardi, Riccardo; Colla, Renata; Pacini, Davide; Traverso, Nicola; Moretta, Alessandro; Pronzato, Maria Adelaide; Bottino, Cristina; et al.
Abstract: Macrophages play a crucial role in atherosclerosis progression. Classically activated M1 macrophages have been found in rupture‐prone atherosclerotic plaques whereas alternatively activated macrophages, M2, localize in stable plaque. Macrophage accumulation of cholesterol and of its oxidized derivatives (oxysterols) leads to the formation of foam cells, a hallmark of atherosclerotic lesions. In this study, the effects of oxysterols in determining the functional polarization of human macrophages were investigated. Monocytes, purified from peripheral blood mononuclear cells of healthy donors, were differentiated into macrophages (M0) and treated with an oxysterol mixture, cholesterol, or ethanol, every 4 H for a total of 4, 8, and 12 H. The administration of the compounds was repeated in order to maintain the levels of oxysterols constant throughout the treatment. Compared with ethanol treatment, the oxysterol mixture decreased the surface expression of CD36 and CD204 scavenger receptors and reduced the amount of reactive oxygen species whereas it did not affect either cell viability or matrix metalloprotease‐9 activity. Moreover, the oxysterol mixture increased the expression of both liver X receptor α and ATP‐binding cassette transporter 1. An enhanced secretion of the immunoregulatory cytokine IL‐10 accompanied these events. The results supported the hypothesis that the constant levels of oxysterols and, in particular, of 27‐hydroxycholesterol stimulate macrophage polarization toward the M2 immunomodulatory functional phenotype, contributing to the stabilization of atherosclerotic plaques. © 2015 The Authors BioFactors published by Wiley Periodicals, Inc. on behalf of International Union of Biochemistry and Molecular Biology, 42(1):80–92, 2016